The inclusion or absence of Pedagogy as a discipline in La Plata and Buenos Aires Universities Higher Education Curriculum (Praxis Educativa, 2012)
The inclusion or absence of Pedagogy as a discipline in La Plata and Buenos Aires Universities Higher Education Curriculum, as a result of reforms since 1984, shows different discourses, practices and point of views of significant agents. The interaction between pedagogical knowledge and educational arena determined the rules and frame of its contents as a discipline. Founded in Bernstein’s categories, the study shows a battle field in which rivalry contents fights to monopolice its specific capital “in” educational arena. Controlling groups imposed educational frames in both universities, legitimating their decisions as being specialized and not arbitrary knowledge, founded and built in their cultural capital in Educational space.
Keywords: pedagogy; Universities Higher; Education Curriculum; educational arena